Hubungan Antara Kontrol Diri Dan Kecemasan Menghadapi Masa Pembebasan Pada Narapidana Di Lembaga Pemasyarakatan Wirogunan Yogyakarta - Faried, Laila; Nashori, Fuad (Khazanah: Jurnal Mahasiswa, 2013)
The purpose of this research was to understand the corelation between selfcontrols and the anxiety of the prisoner to face the liberation. The hypothesis of this research showed that there was negative corelation between self-control and the anxiety of the prisoner to face the liberation. The higher self-control the lower anxiety to face the liberation, so on the contrary, the lower self-control the higher the anxiety to face the liberation. The subjects of this research were men and women prisoners from correctional facility, who would be immediately liberated 5 to 6 months approaching the liberation. The scale which was used in this research was self-control scale, which was arranged by the researcher based on Averiil theory (1973) and anxiety based on Rosenhan and Seligman Theory (1989). The research’s method to analyze the data was SPSS 17.0. This method was used to verify the negative corelation between self-control and anxiety of prisoners to face the liberation. Product moment correlation of Pearson showed the value of r = - 0,451 and p = 0.007 (p>0, 01), which meant there was a significant negative correlation between self-control and anxiety of prisoners to face liberation.